Semiconductor optoelectronic devices introduction to physics and simulation - Piprek, Joachim (Amsterdam ; Boston : Academic Press, 2003)
This book builds a much needed bridge between theoretical and experimental research in optoelectronics by providing both fundamental knowledge in semiconductor physics and real-world simulation examples.
Cover; Frontmatter; I. Fundamentals; II. Devices; Appendix A: Constants and Units; Appendix B: Basic Mathematical Relations; Appendix C: Symbols and Abbreviations; Bibliography; Index.
Includes bibliographical references (p. 251-271) and index.
Keywords: Optoelectronic devices; Semiconductors; Electronic books